Impacto de diferentes condições de ensino no preparo de agentes educativos - Lorena, Angela Bernardo de (2007)
The present study investigated the effects of the training of psychology students in the application of a software developed for teaching reading skills to children with reported academic failure. This training was composed by teaching conditions proposed from the elaboration of a teaching program. These conditions was developed for promoting those children s learning, based on a technology derived from the experimental analysis of behavior in the context special education. For the implementation of the training, the students were presented with different suggested teaching conditions: presentation of the exercises in the classroom; visit to the laboratory, which included a presentation of how the computerized program works; simulation of settings in which the program was applied; participative supervision of the participant s performance; reading of the manual with written instructions. A follow up on the upholding of learning in the participant s performance was also performed with no direct interference by the experimenter (final observation). The teaching conditions were assessed in terms of the contribution of each condition in the development of educational capabilities in the participants, as well as in terms of possibilities of improvement of each condition. The target behaviors (skills to be developed in the participants) were observed and recorded in terms of occurrence, non-occurrence, or aided occurrence; a different set of target behaviors were recorded as they occurred during the sessions of application of the software. The results from 22 participants that were presented with the different conditions of the training program were grouped by the 10 possible sequences of presentation of the conditions. In general, all participants showed an increase in the percentage of target behaviors performed, with a decrease in the percentage of occurrence and aided occurrence recorded between the first and the last condition. In addition, was analyzed the conditions individually (simulation, supervision and final observation) independent of the sequence of conditions to which they were presented. An evaluation of the teaching conditions by the participants was also used, with the assessment of their opinion on the positive and negative aspects of the training. The main conclusions on the relative contribution of each condition were: the simulation condition seemed to be more efficient in reducing the frequency of non-occurrence of the target behaviors; the supervision condition seemed to be more efficient in reducing aided occurrence of the target behaviors; it was not possible to make inferences about the impact of reading the manual, as participants that were not presented with this condition had a similar performance when compared with the participants the were presented with that condition performance of the participants was unstable, which suggests the need for revising relevant aspects to the development of teaching programs; the number of sessions might have played a more important role in the participants performance than the sequence of conditions to which they were presented. Finally, the present study raised important issues to be considered in the training of new agents, and suggests further experiments to investigate the limitations observed.